2011
DOI: 10.1590/s0102-695x2011005000028
|View full text |Cite
|
Sign up to set email alerts
|

Self-organizing maps and VolSurf approach to predict aldose reductase inhibition by flavonoid compounds

Abstract: Aldose Reductase (AR) is the polyol pathway key enzyme which converts glucose to sorbitol. High glucose availability in insulin resistant tissues in diabetes leads into an accumulation of sorbitol, which has been associated with typical chronic complications of this disease, such as neuropathy, nephropathy and retinopathy. In this study, 71 flavonoids AR inhibitors were subjected to two methods of SAR to verify crucial substituents. The first method used the PCA (Principal Component Analysis) to elucidate phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Under diabetic condition, excessive influx of glucose into the tissues results in the increased aldose reductase activity, and thereby increased levels of polyol [ 27 ]. Furthermore, evidences suggest that aldose reductase plays pivotal role in the pathogenesis of diabetic complications such as neuropathy, nephropathy, cataract, retinopathy, and microangiopathy [ 28 ]. Available preclinical and preliminary clinical evidence suggests that inhibition of aldose reductase enzyme activity may be useful in the prevention of onset of diabetic complications [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under diabetic condition, excessive influx of glucose into the tissues results in the increased aldose reductase activity, and thereby increased levels of polyol [ 27 ]. Furthermore, evidences suggest that aldose reductase plays pivotal role in the pathogenesis of diabetic complications such as neuropathy, nephropathy, cataract, retinopathy, and microangiopathy [ 28 ]. Available preclinical and preliminary clinical evidence suggests that inhibition of aldose reductase enzyme activity may be useful in the prevention of onset of diabetic complications [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, evidences suggest that aldose reductase plays pivotal role in the pathogenesis of diabetic complications such as neuropathy, nephropathy, cataract, retinopathy, and microangiopathy [ 28 ]. Available preclinical and preliminary clinical evidence suggests that inhibition of aldose reductase enzyme activity may be useful in the prevention of onset of diabetic complications [ 28 ]. In present study, the MEPG and VAD have showed significant and dose-dependent inhibition of aldose reductase enzyme activity with IC 50 values of 2.050 and 0.788 μ g/mL, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Retinopathy, neuropathy, corneal epitheliopathy and microangiopathy are well-known complications of diabetes mellitus. These complications have been prevented through the inhibition of aldose reductase (Reddy et al 2008;Scotti et al 2011). Our present study on the Pterocarpus marsupium bark extracts showed a significant reduction in aldose reductase activity in the lens of diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory activity ABCG2/BCRP was investigated by VolSurf descriptors [49][50][51] of MIFs. To this end, a library of 34 flavonoids and flavonoid derivatives including flavones, benzopyranes, benzofuranes, boeravinones and acridones were biologically assayed.…”
Section: Mifmentioning
confidence: 99%